Augmented electrical conductivity of hybrid graphene nanoplatelets carbon nanotubes polymer nanocomposites by the electro-magnetic field induced subbands - Mojtaba Haghgoo; Reza Ansari; Mohammad Kazem Hassanzadeh-Aghdam (Journal of Materials Research and Technology)
The performance of polymer-based micro-electronic systems can be evolved by introducing hybrid graphene nanoplatelet (GNP) carbon nanotube (CNT) into the polymer matrix. The electrical conductivity of GNP-CNT polymer nanocomposites is investigated using a conductive network model through electron tunneling considering the subbands effect in an electro-magnetic field. The representative volume element is generated by distributing rode-like CNTs and disk-like GNPs using a Monte Carlo approach. When calculating electrical resistance, the tunneling effect accounts for the electron transfer between each linked pair of nanofillers. The modeling approach consists of the resistance change with the displacement of nanofillers due to strain. When taking into account tunneling behavior in the percolation transition zone, the magnetic field improves the subbands and augments electrical conductivity by transmitting charges. The study reveals that the piezoresistivity of the nanocomposite exhibits a 30% increase at 1.5% strain when the number of subbands is reduced from 20 to 15, or when the aspect ratio is changed from 150 to 100. Additionally, a nanocomposite containing CNTs with a diameter of 20 nm shows a significant increase in conductivity, rising from 10−13 to 10−3 S/m with a 1% increase in volume fraction.